Land Rights and Their Environmental Implications for Indigenous Communities in Nusantara Capital City - Syafitri, Cut Zulfahnur; Kurdi, Kurdi; Rusli, Budiman; Azhari, Azhari (Jurnal Hukum Magnum Opus, 2024)
Article 16A of the IKN Law addresses the extension of land rights periods for business entities. Given the existence of many unrecognized customary law communities in East Kalimantan Province, it is crucial to assess the impact of such extensions on these communities within the IKN (Capital City of Nusantara). This study aims to examine the implications of granting land rights under Law No. 21 of 2023 concerning IKN on the living environment of indigenous peoples in the region. The research employs a normative juridical approach, utilizing both statutory and conceptual frameworks. The findings reveal that Article 16A of the IKN Law, along with its implementing regulations concerning the extension of land rights for business entities, has the potential to adversely affect indigenous communities by exacerbating environmental issues. Specifically, the prolonged extension of land rights diminishes state control over land, accelerates deforestation to the detriment of indigenous communities who rely on forests, increases the risk of water scarcity, and potentially triggers agrarian conflicts and disputes. The study recommends aligning the land rights duration in the IKN Law with that of the Basic Agrarian Law, expediting the local government’s data collection on indigenous communities, involving these communities in decision-making processes, and advocating for the legalization of the Indigenous Peoples Bill.